Desialylation of dying cells with catalytically active antibodies possessing sialidase activity facilitate their clearance by human macrophages. (26th November 2014) - Tomin, A; Dumych, T; Tolstyak, Y; Kril, I; Mahorivska, I; Bila, E; Stoika, R; Herrmann, M; Kit, Y; Bilyy, R
Summary: Recently we reported the first known incidence of antibodies possessing catalytic sialidase activity (sialidase abzymes) in the serum of patients with multiple myeloma and systemic lupus erythematosus (SLE). These antibodies desialylate biomolecules, such as glycoproteins, gangliosides and red blood cells. Desialylation of dying cells was demonstrated to facilitate apoptotic cell clearance. In this study we assessed the possibility to facilitate dying cell clearance with the use of F(ab)2 fragments of sialidase abzymes. Two sources of sialidase abzymes were used: (i) those isolated from sera of patients with SLE after preliminary screening of a cohort of patients for sialidase activity; and (ii) by creating an induced sialidase abzyme through immunization of a rabbit with synthetic hapten consisting of a non-hydrolysable analogue of sialidase reaction conjugated with bovine serum albumin (BSA) or keyhole limpet haemocyanin (KLH). Antibodies were purified by ammonium sulphate precipitation, protein-G affinity chromatography and size exclusion-high performance liquid chromatography (HPLC-SEC). Effect of desialylation on efferocytosis was studied using human polymorphonuclear leucocytes (PMN), both viable and aged, as prey, and human monocyte-derived macrophages (MoMa). Treatment of apoptotic and viable prey with both disease-associated (purified from blood serum of SLE patients) and immunization-induced (obtained by immunization of rabbits) sialidase abzymes, its F(ab)2 fragment and bacterial neuraminidase (as positive control) have significantly enhanced the clearance of prey by macrophages. We conclude that sialidase abzyme can serve as a protective agent in autoimmune patients and that artificial abzymes may be of potential therapeutic value.